EFL Teacher Trainees’ Experiences of Engaging in Online Classroom Interaction During Covid-19 Pandemic - Imannisa Nabilah; Andi Rustandi; Lilies Youlia Friatin (Universitas Galuh, 2023)
This study aims to analyze the experiences of EFL Teacher trainees’ engaging in online classroom interaction during the Covid-19 pandemic and to find out how EFL teacher trainees perceived the benefits of engaging in online classroom interaction during Covid-19 through reflecting on their experiences. This qualitative case study used the data taken from online classroom observation and semi-structured interviews administered to ten EFL teacher trainees in semester two of English education department in one private university in Ciamis. The data analysis of this study was coding and summarizing. This study produced three main points, namely: Challenges and Opportunities for EFL teacher trainees’ experience in engaging online classroom interaction during the pandemic, the most effective strategies to help EFL teacher trainees engaging online classroom interaction, and how EFL teacher trainees perceive benefits in engaging in online classroom interaction during covid-19 through reflecting on their experiences. Based on the findings, engaging in online classroom interaction in a situation like the Covid-19 pandemic where all classes shifted to online mode is crucial. Being active and initiative to interact with instructors, peers, and content helps the learners engage, enjoy, improve and master English in a fun, effective, and efficient way. This experience has reflected the learners to be more independent, disciplined, and aware of how impactful encouragement, feedback, care, and respect are. Thus, it is recommended for English lecturers to create a classroom situation that makes the learners feel comfortable to initiate an interaction using English and improve the technique in teaching-learning activities.